Release and return of repressed people in Lithuania In 1953–1957: between freedom and constraints - Gelžinis, Arvydas (Genocidas ir rezistencija, 2024)
The topic of the article is the release and return of deportees and political prisoners to Lithuania. As the Soviet regime was modifying itself, it abandoned mass repressions as of 1953 and authorised a large part of the deportees to return home. According to the available information, in 1953–1958 over 40,000 people returned to Lithuania from exile and imprisonment. The release of political prisoners within the context of USSR’s repression is clearer. The release of a political prisoner could happen in three scenarios: (i) after serving the full sentence, (ii) prematurely, i.e. after serving 2/3 of the sentence, or (iii) after serving a fixed period in exile following the sentence at the labour camp, which was usually 5 years. The specific period of deportation was not fixed, the Soviet perpetrators used the term ‘na viečno’ (for eternity, forever). As a result, the communist authorities and repressive structures had to take various decisions to release the deportees: they had to adopt many orders and resolutions, and the fate of each family had to be decided by the commissions for the review of deportees’ cases. Therefore, in light of these complex procedures, the article focuses more on the release of the deportees.This paper examines the cooperation between the Lithuanian Communist Party and the repressive structures in their attempts to ensure a gradual return of deportees and political prisoners, as the return of the repressed was raising great concern for the Soviet authorities. Such concerns mainly resulted from the fact that some of the repressed were entitled to restitution of confiscated property (often no longer available), while there was a potential threat that a sudden or massive return of these people would incite the anti–Soviet sentiment in Lithuania. Research into the activities of the commissions for the review of deportees’ cases was based on archival documents. Both statistical data and deliberations of the fate of individual families by the commissions are presented in this paper. The analysis of the sources demonstrates a significant change as of 1956 triggered by several driving factors: the growing number of repressed returnees, the news of the 1956 Hungarian anti-Soviet uprising reaching Lithuania, and anti-Soviet demonstrations in Kaunas and Vilnius during the 1956 All Souls’ Day. Sensing danger the Lithuanian communist authorities took some precautionary measures. In January 1957, a decree banned the return to Lithuania of prominent Lithuanian statesmen, leaders of the armed resistance and anti–Soviet underground. At the same time, the returned deportees and political prisoners were ‘under supervision’ by strengthening the repressive apparatus of the LSSR’s KGB, by preventing the returnees from registering, from getting a job, and by prohibiting them from returning to their hometowns. In this way, the communist authorities achieved their goal: some of the returnees, unable to settle, went to Latvia, the Kaliningrad region, or even back to Siberia, where they had a guaranteed employment. In this way, the Lithuanian communist government tried to create a ‘critical mass’ of the Lithuanian population which it could lead towards a ‘bright communist future’.
Keywords: bureau of the LSSR’s Central Committee; LSSR’s Council of Ministers; Supreme Soviet of the LSSR; Soviet repressions; deportees; political prisoners; commission for the review of deportees’ cases; release; return; constraints; isolation of the formerly repressed population